2018
DOI: 10.1001/jamanetworkopen.2018.2908
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Opioid Prescribing Practices Before and After Implementation of a Health System Intervention to Reduce Opioid Overprescribing

Abstract: Key Points Question Can a series of focused interventions targeting different aspects of opioid overprescribing reduce opioid overprescribing within a health system? Findings This quality improvement study found postintervention reductions in opioid prescribing occurred at a statistically significantly faster pace than a preintervention downward trend. Overall reductions for key measures were 58% for morphine milligram equivalents per clinical encounter per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 30 publications
3
96
0
1
Order By: Relevance
“…If a surgeon believes that opioid dependence/abuse is not a problem, then they might choose to prescribe opioids more frequently, and vice-versa. [6][7][8] A similar survey study to this one, looking at attitudes of hand surgeons regarding opioid use, revealed that most hand surgeons (76%) felt that opioid abuse was a big/moderate problem in the hand surgery community. 9 Resultantly, almost half of the same population reported that they were less likely to prescribe opioids when compared to 1 year prior.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…If a surgeon believes that opioid dependence/abuse is not a problem, then they might choose to prescribe opioids more frequently, and vice-versa. [6][7][8] A similar survey study to this one, looking at attitudes of hand surgeons regarding opioid use, revealed that most hand surgeons (76%) felt that opioid abuse was a big/moderate problem in the hand surgery community. 9 Resultantly, almost half of the same population reported that they were less likely to prescribe opioids when compared to 1 year prior.…”
Section: Discussionmentioning
confidence: 66%
“…If a surgeon believes that opioid dependence/abuse is not a problem in that patient or patient population, then he/she might choose to prescribe opioids more frequently, and vice-versa. [6][7][8] A previous study has demonstrated that when surgeons perceive opioid abuse to be a big/moderate problem among their patients, a subsequent reduction in opioid prescription ensues. 9 While opioid prescription patterns among facial plastic surgeons after rhinoplasty have been previously reported, [2][3][4] no research has evaluated the perceptions of facial plastic surgeons on opioid dependence in the rhinoplasty population.…”
mentioning
confidence: 99%
“…Our findings provide priority areas that clinicians, policymakers, medicine regulators, and commissioners can use in their plight to manage the growing opioid crisis. Monitoring the prescribing of opioids via clinical dashboards or electronic medical records has improved adherence to guidelines, reduced opioid doses, and improved physicians' knowledge and attitudes towards managing people on opioids in primary care [40][41][42]. Strategies that promote the safe prescribing of opioids and enable prescribers to effectively manage factors such as benzodiazepine co-prescription and depression are needed.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…29 Recently, mandatory prescription limits have been associated with a reduction of opioid use after elective surgeries. [30][31][32][33] However, our knowledge of the potential strategies is limited, and none are currently broadly applied as standard of care interventions. The objective of our scoping review is to understand the strategies aiming at preventing chronic opioid use specific to adult trauma and acute care surgery patients.…”
Section: Open Accessmentioning
confidence: 99%